Modeling the Relationship Between Exchange Rate Instability and Economic Performance in African Countries - Innocent Simji, Lumpye; M.O, Adenomon; B, Maijama’a (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Exchange rate volatility has created an unstable environment for most factors, such as investment and economic performance. It has, however, severely affected most countries in Africa, which rely on primary export and essential imports. This research investigated exchange rate variability’s impact on economic performance in Africa. It sought to apply macroeconomic variables in Standard GARCH and Panel ARDL models; measure exchange rate volatility through the Ggeneralized Autoregressive Heteroskedasticity model; and assess short-run and long-run exchange rate movements: Ex-post facto design research design was adopted, covering the period 1990 to 2023 employing the econometric techniques of GARCH model, panel unit root tests (IPS and LLC), and panel cointegration methods. Pooled Mean Group (PMG) model was used to determined the most appropriate for interpretation using Hausman test results. The output indicated that while the exchange rate value (1.3071) had a positive impact, exchange rate volatility (-0.2784) and inflation (-0.3647) were negatively impacting long-run economic performance. Interest rates also had a positive but statistically insignificant effect (0.2022). In the short run, interest rates positively influenced economic performance (0.0818), while inflation (-0.0707) and exchange rates (-0.6945) had negative effects. Exchange rate volatility (-0.0764) was insignificant. The ECM of (-0.2934) shows that the long-run equilibrium will be restored by a factor of 29% annual correction rate. Recommendations include more stringent inflation-targeting measures that could lessen adverse effects on economic performance. Strengthening(CBN) capacity to maintain price stability is particularly important in interest rate management and open market operations, which would improve economic performance.